THE POTENTIAL UTILIZATION OF RASAU FIBER (Pandanus helicopus) AS AN ALTERNATIVE NON-FOOD INDUSTRY MATERIAL TOWARDS A CREATIVE ECONOMY - Nur A’in, Latifah; Jumrodah; Supriatin, Atin (Universitas Medan Area, 2024)
Pandanus helicopus is one of the fibrous plants that is considered a nuisance so that its utilization is still lacking. Meanwhile, P. helicopus's fiber has the potential to be used in industry, especially in the manufacture of food brushes. The objective of this study is to identify the potential of P. helicopus's fiber, which is used as an alternative to non-food industrial materials, especially brushes that are halal toward the principle of creative economy. This study is experimental research by combining two methods, there are exploration and experiment laboratory. The results showed that P. helicopus leaf fibers have the characteristics of fibers that are quite fine, strong and elastic. Based on the laboratory tests, it was found that fibers became stronger and finer when given immersion treatment in NaOH solution with the most effective concentration of 7.5% with the test results of a fineness level of 2462.88 Tex, a tenacity value of 145.07 mN/Tex and 14.80 gf/Tex, and fiber elasticity of 19.56%. The characteristics of P. helicopus leaf fiber has the potential to be used as an alternative material in the industrial field, especially in the manufacture of halal plant fiber brushes. The utilization of P. helicopus's fiber in industry can be a creative innovation that can realize the principles of creative economy.